The Impact of Partners' Economic Incentives on Audit Quality in Big 4 Partnerships - Dekeyser, Simon; Gaeremynck, Ann; Knechel, W. Robert; Willekens, Marleen (The Accounting Review, 2021)
ABSTRACT Economic incentives are fundamental for understanding auditor behavior. In this paper, we investigate the association between the extent of partners' fee-based compensation, partners' observable net wealth, and audit quality. Using a sample of Belgian Big 4 audit firms and their predominantly private clients, our results suggest a negative association between audit quality and partner fee-based compensation, and a positive association between audit quality and partner observable net wealth. Moreover, our results show that the latter association is most significant when a partner is carrying a lot of debt, which indicates that a partner's financial situation may affect audit quality. The extent of fee-based incentives also varies among partners of the same audit firm. Furthermore, partner and client characteristics differ based on the extent of fee-based compensation. Our findings should be of interest to regulators and audit firms, as they suggest that audit partners' economic incentives significantly affect audit quality. Data Availability: All data are publicly available from the sources identified in the text. JEL Classifications: M41; M42; D81.